Extension and Modernisation of the German School of Lisbon. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
The Lisbon German School was designed in 1961 by Oto Bartning, one of the most important German architects of the 20th century, for an area of over three hectares, then characterized by a predominantly rural landscape, outside the urban limit of the city. In 2003 it already contained several additions that deprived it of its character, while it was surrounded by a dense and noisy urban environment. The intervention was essentially therapeutic, intensifying the protagonism of the original complex. However, it was based not only on the recovery of the pre-existing buildings – including the demolition of the later interventions – and their adaptation to the new needs – introducing new infrastructures and coverings (promoting an acoustic and thermal optimization of the whole) – but also the construction of some buildings. A new gymnasium – a pure prism, which follows the auditorium building, limiting and qualifying a new entrance square to the school – was built, as well as a new building dedicated to the elementary school – which now delimits the playground area, creating a barrier to the noise produced by the intense traffic of the Segunda Circular. While the new gymnasium has a roof materialized with “shed” type beams, with a concrete slab between each pair, in mixed structural operation, the new primary school has a roof entirely in reinforced concrete, providing a wooded volume for noise protection. The new playground – covered but open – has a striking translucent polyvinyl chloride roof.